2019
DOI: 10.1080/02670844.2019.1597426
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of novel binderless anode via electrophoretic deposition for HT-PEMFC

Abstract: We report a simple strategy to fabricate electrodes for high temperature electrolyte membrane fuel cell (HT-PEMFC) by eliminating binder. The Electrophoretic Deposition (EPD) method was used to fabricate the Gas Diffusion Electrode (GDE) in the absence of the binder. For comparison, the same catalyst ink was used to make hand-spray binderless electrode, and both electrodes used as anodes for Membrane Electrode Assemblies (MEAs) in a HT-PEMFC operating at 140°C. XRD and SEM were used to investigate the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This study demonstrated a pathway and methodology to improve MEA performance by optimizing ionomer composition, structure, and networks in the catalytic layer. The electrophoretic deposition (EPD) method, with considerable results in fabricating the gas diffusion electrode (GDE) in the absence of the binder for membrane–electrode assemblies (MEAs) in PEMFC operating at 140 °C, is presented in this article [ 312 ].…”
Section: Membrane–electrode Assembly (Mea): Preparation and Characterizationmentioning
confidence: 99%
“…This study demonstrated a pathway and methodology to improve MEA performance by optimizing ionomer composition, structure, and networks in the catalytic layer. The electrophoretic deposition (EPD) method, with considerable results in fabricating the gas diffusion electrode (GDE) in the absence of the binder for membrane–electrode assemblies (MEAs) in PEMFC operating at 140 °C, is presented in this article [ 312 ].…”
Section: Membrane–electrode Assembly (Mea): Preparation and Characterizationmentioning
confidence: 99%
“…[493][494][495][496][497][498][499] Cross-sectional SEM is a useful technique to assess membrane and electrode thickness, pore size distribution, catalyst location, catalyst layer structure and defects. 70,103,127,161,378,380,488,489,[493][494][495][499][500][501] For HT-PEMFCs this has been shown to be useful for tracking acid loss out of the membrane via thickness changes. 380 Crosssectional SEM has also been shown to signicantly improve understanding of structural degradation during ASTs by observing the direct impact of the MEA thickness, pore structure, catalyst migration and support degradation.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Binderless catalyst layer: interestingly, acceptable performance has been reported by using catalyst layers without any binder or filler, creating a PA interface between the membrane and catalyst layer using the capillary force within the catalyst layer [283,295,308,309]. Promising durability was achieved at 0.2 A cm −2 in HT-PEMFCs [295], with 900 h stability at 0.2 A cm −2 , and the high loading used (0.96 mg Pt cm −2 ) may have created a barrier to PA leaching.…”
Section: Pa Diffusion In the Electrodementioning
confidence: 99%